Ações Socioeducativas como Práticas de Inovações Sociais: Um Estudo de Caso - Evandro Schutz (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
This article seeks to analyze if the socio-educational activities carried out by the Institute Engevix social innovation practices can be considered. This Institute develops actions in education, seeking to meet certain portion of a community of Florianópolis living in a situation of economic and social vulnerability. The research consists of a case study developed together with key informants and beneficiaries of the project. To support this research, theoretical views of the conceptions of social and educational activities and social innovations were discussed, trying to detect possible links between them. Overall, both the social and educational activities as social innovations of practical help in the social development process. Even can exist as two independent processes there is the possibility of convergence and fusion there between. Research shows that while not unique, the socio-educational project sponsored by the Institute Engevix is configured in a practice of social innovation as it contributes to social inclusion of individuals who participate in it. It appears, however, to the theoretical further research there in the project, a jarring aspect in relation to defining lines of the practices of social innovation. It is the absence of more autonomous and active participation of the community attended the directions and decisions taken by the project. Finally, interest in developing this study is anchored mainly on the possibility of contributing to the current debate within the administration, of the constitutive inclusive processes of the actions of social innovation.